Teacher performance in civic and ethical formation: Empirical study and educational policy recommendations for junior high school in Mexico - Francisco Urrutia (Arizona State University, 2020)
The purpose of this article is to expose the process and results of a research on a study on teacher practices in order to understand the opportunities and ways to improve their performance in the class on civics and ethics. The author carried out teacher performance analysis and assessment on the basis of a methodology for the qualitative analysis of classroom situations and a model of standards for teacher performance in the classroom. The study allowed the author to build a series of recommendations for policy decisions, oriented to the improvement of teacher performance. The teaching practice elements defined as connection among subjects, differentiated attention, student-to-student assessment, and self(student)-assessment received the lowest scores among the group of evaluated teachers. Thus, Mexican teachers require training and support in these specific elements. The elements with the highest scores for the evaluated teachers were: student-student learning relations, didactic resources, directed activities, interpersonal relationships and teacher's assessment of students The standards for teacher performance in the classroom and its evaluation model have proven to be relevant and useful tools for diagnosing the need for improvement in teaching practice, and therefore for reporting the training and technical assistance required by teachers and schools.